1980
DOI: 10.1007/bf02618333
|View full text |Cite
|
Sign up to set email alerts
|

Cell culture of infantile digital fibromatosis

Abstract: Two cell cultures were obtained from excised tumors of two cases of infantile digital fibromatosis (IDF). The cells had eosinophilic cytoplasmic inclusion bodies characteristic of IDF. Although the rate of cells bearing the inclusion bodies was high at the earlier passage levels, it was reduced to zero by the 15th passage of one of the cultures, but the cells of the other culture continued to produce the inclusion bodies even at the 30th passage. Chromosome analysis revealed both cultures to have tetraploid ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Smooth muscles cells, however, show myofilaments scattered throughout the cell cytoplasm (Bhawan 1981). Electron microscopy and tissue culture findings have elimi-nated the possibility of viral origin of the round inclusion bodies (Mehregan et al 1972, Burry et al, 1970, Miyazono et al, (1980), utilizing tissue cultures, demonstrated that round inclusion body formation by the tumor fibroblasts persists for as much as 30 passages. Recurring digital fibrous tumor is benign, and no metastatic lesions have been reported.…”
Section: Recurring Digital Fibrous Tutnor Of Childhoodmentioning
confidence: 99%
“…Smooth muscles cells, however, show myofilaments scattered throughout the cell cytoplasm (Bhawan 1981). Electron microscopy and tissue culture findings have elimi-nated the possibility of viral origin of the round inclusion bodies (Mehregan et al 1972, Burry et al, 1970, Miyazono et al, (1980), utilizing tissue cultures, demonstrated that round inclusion body formation by the tumor fibroblasts persists for as much as 30 passages. Recurring digital fibrous tumor is benign, and no metastatic lesions have been reported.…”
Section: Recurring Digital Fibrous Tutnor Of Childhoodmentioning
confidence: 99%